2017
DOI: 10.37358/rc.17.8.5796
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Zirconia-Prefabricated Crowns in Children with Primary Dentition

Abstract: Zirconia dioxide represents the current alternative in restoring primary teeth, being the most promising restorative material through its properties that offer. Zirconia crowns main properties are its aesthetics, resistance to fracture and compression, biocompatibility, alternative for the patients that are allergic to Ni-Cr. This cross-sectional study pointed out the correlations between the rate of applicability of the Ni-Cr crowns and the ZrO2 crowns, as well as the range of applicability of the ZrO2 crowns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 8 publications
1
11
0
2
Order By: Relevance
“…Zirconia crowns were least preferred among the study population (0.46%). Similar indings were shown in a previous study by Bica et al (2017); M. G. , where it was seen that zirconia crowns had better clinical performance and less plaque deposition when compared to stainless steel crowns. But, this is contradictory to indings of a study by Abdulhadi (2017), which showed that zirconia crowns had good aesthetics and stressbearing capacity and was highly preferred.…”
Section: Resultssupporting
confidence: 89%
“…Zirconia crowns were least preferred among the study population (0.46%). Similar indings were shown in a previous study by Bica et al (2017); M. G. , where it was seen that zirconia crowns had better clinical performance and less plaque deposition when compared to stainless steel crowns. But, this is contradictory to indings of a study by Abdulhadi (2017), which showed that zirconia crowns had good aesthetics and stressbearing capacity and was highly preferred.…”
Section: Resultssupporting
confidence: 89%
“…According to the authors Bica (2017) and Ashima (2014), zirconia crowns have properties such as aesthetics, translucency, fracture and compression resistance, biocompatibility, thermostable. In addition, they have the possibility of adapting the crown only when traveling to the dental office, can be used in the autoclave and are a great alternative for patients allergic to Ni-Cr alloys (nickel and chromium) 4,11 . Shuman (2016), still brings that it has very low thermal conductivity, high impact resistance, high chemical resistance (both acids and bases) and high wear resistance 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Among its properties, are: aesthetics, fracture and compression resistance, biocompatibility, possibility of adapting the crown only when traveling to the dental office, can be used in the autoclave and are an alternative for patients allergic to alloys. nickel and chromium 11 . In addition, it has very low thermal conductivity, high impact resistance, high chemical resistance (both to acids and bases) and high wear resistance 3 .In addition, zirconia is able to prevent the increase of cracks¹ 5 and is resistant to fractures, this is possible because the crystals of the tetragonal zirconia are transformed into the monoclinic form producing tension compression 16 .This characteristic makes it possible for this material to have a wide application of clinical success 15 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations